Three-dimensional quantitative analysis of dental and skeletal characteristics of skeletal Class I unilateral posterior crossbite in adults - Jingwen Wu; Joanna Ser Yun Bek; Mengqi Luo; Hao Xu; Yanmin Wang; Xianglong Han (BMC, 2022)
Abstract Background To study the dentoskeletal characteristics and the degree of compensations in skeletal Class I adults with unilateral posterior crossbite (UPCB). Methods A sample of 40 adults was chosen for this cross-sectional study. 20 skeletal Class I adults with UPCB (mean age: 22.20 ± 2.88 years), were compared to 20 skeletal Class I adults with normal occlusion (mean age: 27.56 ± 5.76 years). The respective dentoskeletal measurements were made on cross-sectional images from cone-beam computed tomography scans. Results Skeletally, both groups showed significant differences (P < 0.05) in mandibular corpus length and menton deviation with the UPCB group showing the greatest displacement. Maxillomandibular vertical asymmetry and condylar positional asymmetry were not significant in both groups (P > 0.05). For dental variables on the second premolar and first molar, the UPCB group showed greater linear and angular differences when compared to the control group (P < 0.05). On the crossbite side, maxillary posterior teeth were more buccally inclined, and mandibular posterior teeth were more lingually inclined. However, on the non-crossbite side, both maxillary and mandibular posterior teeth were lingually inclined. Conclusion Adults with UPCB showed distinct transverse dentoskeletal asymmetry. No asymmetry was found in the condylar position and the mandibular height in UPCB adults.